Univents: an eID IT system - Bousios, Nikolaos; Chasiotis, Konstandinos; Μπούσιος, Νικόλαος; Χασιώτης, Κωνσταντίνος (2020)
Ο πηγαίος κώδικας για το API, το Android App και το Angular Application βρίσκονται στο Github αντίστοιχα https://github.com/Rambou/Univent https://github.com/Rambou/Univent-app https://github.com/Armageddonas/Univent-Web-App